Solitary fibrous tumor with IGF-II-induced non-islet cell tumor hypoglycemia: a case report and molecular characterization by next-generation sequencing - Niedra, Helvijs; Konrade, Ilze; Peculis, Raitis; Isajevs, Sergejs; Saksis, Rihards; Skapars, Roberts; Sivins, Armands; Daukste, Beate Elizabete; Mezaka, Dace; Rovite, Vita (Frontiers in Oncology, 2023)
Background Non-islet cell tumor-induced hypoglycemia (NICTH) is a rare, life-threatening medical condition caused by excessive insulin-like growth factor II (IGF-II) secretion from tumors of most commonly mesenchymal origin. Using next-generation sequencing, we have characterized the genome and transcriptome of the resected IGF-II-secreting solitary fibrous tumor from a patient with severe hypoglycemia accompanied by hypoglycemia unawareness. Case presentation A 69-year-old male patient presenting with abdominal discomfort was examined using computer tomography, revealing a large lesion at the lesser pelvis extending above the umbilicus. As no bone and lymph node metastases were detected, the patient was scheduled for laparotomy. Before surgery, the patient presented with symptoms of severe hypoglycemia. Suppressed C-peptide levels and subsequent hypokalemia indicated a possible case of NICTH. The patient was treated with methylprednisolone (8 mg) to assess hypoglycemia. After the surgery, mild hypoglycemia was present for the postoperative period, and no radiological recurrences were observed 3 and 12 months after discharge. Histopathological examination results were consistent with the diagnosis of malignant solitary fibrous tumor (SFT). Overexpression of IGF-II was confirmed by both immunohistochemistry and RNA sequencing. Further NGS analysis revealed an SFT characteristic alteration—NAB2-STAT6 fusion. Additionally, three deleterious missense variants were detected in oncogenes BIRC6, KIT, and POLQ, and one homozygous in-frame deletion in the RBM10 tumor suppressor gene. Conclusion While the NAB2-STAT6 fusions are well characterized, the mutational landscape of SFTs remains understudied. This study reports the importance of NGS to characterize SFTs as we detected four coding variants in genes (BIRC6, KIT, POLQ, and RBM10) associated with tumorigenesis that could potentially contribute to the overall pathogenesis of SFT.